Vertical distribution, population density, and natural egg parasitism of cotton leafworm on cotton under IPM - FERNANDES, MARCOS GINO; S. MOREIRA, MÁRIO ADRIANO; DEGRANDE, PAULO EDUARDO; CUBAS, ANTÔNIO CARLOS; SILVA, ANDERSON MIGUEL (Revista Colombiana de Entomología, 2007)
Alabama argillacea is one of the most important pests of cotton crops in Brazil, and therefore it is necessary to research its behavior and natural biological control in areas under IPM conditions to improve the management of its population. In the pursuit of this objective, experiments were carried out on cotton crops in Dourados, Mato Grosso do Sul, in the 1997-1998 growing season. With the object of determining the population density and vertical distribution of eggs, larvae, and pupae, the total number of eggs, small, medium and large sized larvae and pupae found on the upper, middle, and lower sections of the plants were weekly recorded. This was conducted in an area where pest management was done according to IPM techniques and tactics. In the same area, eggs of this species were also gathered to determine the proportion of parasitism. The pest lays the majority of eggs on the upper part of the plants where the majority of midand large-sized larvae were also found. Small larvae were generally found on both middle and lower parts of the plants. A growing percentage of parasitism by Trichogramma pretiosum was found from the beginning through the end of the crop season, reaching almost 100% parasitized eggs by the end of plant development. The average number of eggs found per plant was high during almost the whole crop cycle, reaching about 30 eggs per plant by the end of the cycle. The total number of small caterpillars was high and constant during the whole evaluation period, while medium and large ones were more abundant in the final phase of the crop cycle. The total caterpillar population reached peaks of around four caterpillars per plant.